Effect of Compensation and Benefit on Employee Performance with Motivation as Moderating Variable - Cahyo Prihantoko; Agatha Ferijani (Soegijapranata Catholic University, 2021)
Banking industry is currently experiencing a new demographic era known as the era of demographic bonus which occurs due to changes in the age structure of labor. This demographic bonus also occurs in Bank X in Semarang in which all funding officers in the marketing department are aged between 20 and 38 years old which is known as generation Y or millennial generation. The purpose of this study was to analyze the influence of compensation and benefits on employee performance and whether motivation moderates the influence. The population in this study were all funding officers in the marketing department, totaling 121 employees and all of them were selected as the sample. The type of data used is primary data obtained from the respondents by means of questionnaires. The classical assumption tests used in this study include normality, multicollinearity, and heteroscedasticity tests. The analytical tool used in this research is the Moderated Regression Analysis (MRA) test. The results indicate that compensation and benefits affect employee performance and motivation moderates the effect of compensation and benefits on employee performance.